Comparison of conventional bacteriology with nucleic acid amplification (amplified mycobacterium direct test) for diagnosis of tuberculous meningitis before and after inception of antituberculosis chemotherapy. - Thwaites, G; Caws, M; Chau, T; Dung, N; Campbell, J; Phu, N; Hien, T; White, N; Farrar, J (2004)
The role of nucleic acid amplification techniques in the rapid diagnosis of tuberculous meningitis remains uncertain. We compared the performance of Ziehl-Neelsen (ZN) staining, the Gen-Probe amplified Mycobacterium tuberculosis direct test (MTD), and culture with 341 cerebrospinal fluid specimens from 152 adults (73 with and 79 without tuberculous meningitis) before and after inception of antituberculosis chemotherapy. The sensitivity, specificity, and positive and negative predictive values of ZN staining before treatment were 34/66 (52%), 79/79 (100%), 34/34 (100%), and 79/111 (71%), compared with 25/66 (38%), 78/79 (99%), 25/26 (96%), and 79/120 (66%) for MTD. The sensitivity of combined ZN staining and MTD (either positive) was 45/66 (68%). The sensitivity of staining and culture fell more rapidly than that of MTD after the start of treatment: after 5 to 15 days of treatment, MTD was more sensitive than ZN staining (12/43 [28%] versus 2/43 [2%]; P = 0.013). Slower bacterial clearance was observed if M. tuberculosis was resistant to isoniazid and/or streptomycin: resistant organisms were more likely to be cultured from cerebrospinal fluid after 2 to 5 days of treatment than fully sensitive organisms (P < 0.001). The sensitivities of ZN staining, MTD, and the two tests combined were improved by repeated sampling to 38/59 (64%), 35/59 (59%), and 49/59 (83%), respectively. In conclusion, ZN staining of the cerebrospinal fluid is at least as good as MTD for the rapid diagnosis of tuberculosis and is much faster and less expensive. However, the combination of these methods on serial samples detects more cases. Alternative tests are still urgently required.